2020
DOI: 10.1111/cen.14262
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium intake and cortisol measurements

Abstract: The average dietary sodium intake of adults living in the United States is estimated to be 3600 mg per day. 1 This is higher than the 2019 Institute of Medicine guidelines that recommend an upper limit of 2300 mg of sodium per day in adults and substantially greater than American Heart Association guidelines, which target an upper limit of 1500 mg per day. 2,3 Higher dietary sodium intake induces a range of physiological changes including intravascular volume expansion, increased glomerular filtration rate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Urinary excretion of cortisone and other cortisol metabolites are also thought to be affected by declining renal function. Additionally, increased dietary sodium consumption has been shown to increase urinary free cortisol excretion [35] . In clinical scenarios such as these, measuring cortisol using another sampling method would be a better option.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of cortisone and other cortisol metabolites are also thought to be affected by declining renal function. Additionally, increased dietary sodium consumption has been shown to increase urinary free cortisol excretion [35] . In clinical scenarios such as these, measuring cortisol using another sampling method would be a better option.…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis was activated and the forward response to environmental stress amplified, whereas the capacity to buffer blood corticosterone through binding to CBG was reduced. This study provides an explanation of the positive correlation between salt intake and urinary cortisol excretion consistently observed in humas [12][13][14][15][16][17][18] , and has two important implications. First, glucocorticoid excess may contribute to the long-term health consequences of high salt intake; second, dietary salt intake becomes an important consideration when diagnosing and managing preexisting hypercortisolism.…”
Section: Discussionmentioning
confidence: 88%
“…The copyright holder for this preprint this version posted March 5, 2022. ; https://doi.org/10.1101/2022.03.04.481654 doi: bioRxiv preprint excretion [12][13][14][15][16][17] . A long-term balance study also found a positive relationship between salt intake and urinary cortisol excretion in healthy men enrolled in the MARS-500 spaceflight simulation programme 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…blood pressure, oxidative stress and vascular endothelial dysfunction; although the underlying mechanisms have not been fully elucidated [3]. Multifactorial combination of genetic, environmental, modifi cation in lifestyles and complex web of intravascular interactions of vasoactive substances and dietary factors other than sodium can play a role in the degree and etiology of persistent elevation in blood pressure in rodents and humans [4][5][6]. Experimental animal models have shown that Sprague-Dawley rats [(SDR, (inbred)] rapidly develop high blood pressure (>170 mm Hg) when fed 8% NaCl diet [7][8][9].…”
mentioning
confidence: 99%